Evaluation of Project Management Methodologies Success Factors Using Fuzzy Cognitive Map Method: Waterfall, Agile, And Lean Six Sigma Cases - Dursun, Mehtap; Goker, Nazli (International Journal of Intelligent Systems and Applications in Engineering, 2022)
A methodology for project management refers to a set of guidelines that defines how to work and communicate while working as a project member. Waterfall practice is the old methodology. As a response to dealing with the difficulty of software development, it has turned out to the most widely utilized methodologies of project management in the software and management industries. Oher software development focused project management method, Agile, has appeared as a response to the shortcoming of Waterfall tool for handling complex projects. Lean Six Sigma is the combination of the main strategies of Six Sigma and Lean. This paper aims to reveal success factors of these three project management methodologies employing Fuzzy cognitive map (FCM) technique, which combines fuzzy logic and neural networks. Presence of cause-and-effect relationships between pair of success indicators and unavailability of crisp data led us to use FCM method in order to determine the most significant criteria of these project management methodologies. This is the first study that considers multiple and conflicting criteria of success factors of waterfall, agile, and lean six sigma project management methodologies. There is no study that aims to provide success criteria evaluation of waterfall, agile, and lean six sigma project management methodologies. This assessment is crucial for companies that have to be managed effectively their project processes in increasing technology and market competition. FCM is a suitable tool to solve this problem since it considers positive and negative relationships, causal links among criteria with their direction, and it is applicable in the absence of crisp data.